Where Environmental Citizen Science Meets the Law - Dick Kasperowski; Anna Berti Suman; Shun-Ling Chen; Christopher Kullenberg (Citizen Science: Theory and Practice, 2023)
Editorial for the special collection Where Environmental Citizen Science Meets The Law.